ESTABLISHING STUDENT CHARACTER IN ISLAMIC RELIGION-BASED SCHOOLS - Fredy Yunanto (Universitas Pahlawan Tuanku Tambusai, 2022)
Character building is very important for us to review, because character building is one form of the government's efforts to develop the next generation of young people with character. To make this happen, support from all parties is needed, one of which is the educational forum. Education can be used as one of the perfect solutions to shape and develop the personality of students. Even so, there needs to be extra effort from educators so that this can be done. Within the scope of character education can be made through personal learning that is also not exclusive and is carried out continuously so that students can know and practice it in everyday life. Keywords: Student Character, Based On Islamic Religion